Rapid pleurodesis using small bore pigtail catheter and bleomycin in malignant pleural effusions: a case series - Md Hashim , Mohd Nizam (2009)
Pleural drainage is the treatment of choice for patients presented with symptomatic malignant pleural effusion. The conventional method of treatment is insertion of large bore thoracostomy tube (chest tube) before proceeding to chemical pleurodesis. The aim of this preliminary prospective study was to investigate the success rate of performing pleurodesis using a small bore pigtail catheter (Mar Flow® CH12) in patients with malignant pleural effusion. Pleurodesis was performed within twenty four hours after insertion of pigtail catheter with bleomycin as sclerosing agent. Patients were follow-up at four weeks post pleurodesis with chest radiography. The intervention was scored as “successful” if no radiographic evidence of fluid reaccumulation was noted at four weeks. A “partial success” score indicated accumulation of fluid that did not produce symptoms and did not require repeat pleural drainage of any sort. All other outcomes were scored as “unsuccessful”. Five patients with malignant pleural effusion from Hospital Universiti Sains Malaysia and Hospital Raja Perempuan Zainab II were included in this study with mean age of 53.6 year old. The primary diseases include breast, lung, ovarian and colon cancers. The mean time of pleurodesis was 9.5 hours. Of the five pleurodesis performed, a complete response (“successful”) was seen in three patients (60%), a partial response (“partial success”) was seen in one patient (20%) and one patient (20%) did not respond to rapid pleurodesis. In conclusion, pleurodesis in patients with malignant pleurodesis can be achieved rapidly using small bore pigtail catheter and bleomycin.